Removal of Sulphate and Heavy Metals from Acid Mine Drainage using Permeable Reactive Barrier Technique - Anungstri, Rissa; Petrus, Himawan Tri Bayu Murti; Prasetya, Agus (2022)
Containing sulphates and heavy metals, acid mine drainage (AMD) should be managed strategically to mitigate and control the migration of the contaminants to the downstream area. Conventional treatment techniques such as using lime to increase pH levels and metal precipitation or using imported material are usually inefficient and unsustainable. The AMD treatment investigated in this study uses the permeable reactive barrier (PRB) technique to enhance bacterial sulphate reduction and metal sulphide precipitation. The AMD treated is seepage water from industrial mining waste rock dump. This study aims to calculate the removal efficiency percentage of reactive materials to reduce contaminants in a batch test. Reactive materials used were organic waste generated locally i.e. domestic sewage sludge (SE), municipal compost (CO), cocopeat (CP), and the inorganic waste material is fly ash (FA) from a coal-firing power plant. A batch test was conducted in 56 days in an anaerobic chamber using nitrogen gas to support an anaerobic environment during subsampling. Mine water used in this test has a low pH level of 3.2, alkalinity (as CaCO3) < 1 mg/L, high sulphate 3280 mg/L, and contains Fe 46 mg/l, Al 54 mg/L, Cu 2.3 mg/L and Zn 3.4 mg/L. The test result at day 56 from using individual reactive material shows increased pH levels to 6.9; 5.6; 3.7; and 11.6 for sewage (SE), compost (CO), cocopeat (CP), and fly ash (FA), respectively. Alkalinity was increased to 1450 mg/L (SE), 323 mg/L (FA), 15 mg/L (CO), 1 mg/L for CP. The highest sulphate removal was measured in 85 from addition of FA. Sulphate removed from organic material reactor were 52 by (SE), 17 by (CO), 20 by (CP). RE of dissolved metals (Al, Cd, Co, Mn, Ni, Fe, Cu, Zn), from SE reactor was 80, CO reactor 80, CP reactor 52, FA reactor 94. Oxidation-Reduction Potential (ORP) was measured to determine reducing conditions. ORP were measured at -551 mv, 255 mv, 156 mv, and -113 mv for SE, CO, CP and FA respectively. SE has the potential to remove metals and favour reducing conditions for sulphide precipitation at medium pH levels. Meanwhile, metal precipitation from addition of FA is mainly due to hydroxide precipitation at high pH levels. FA was able to decrease the most sulphate due to ion adsorption. © Published under licence by IOP Publishing Ltd.